Photoluminescent carbon dots as biocompatible nanoprobes for targeting cancer cells in vitro - Li, Qin; Ohulchanskyy, T.; Liu, R.; Koynov, K.; Wu, D.; Best, A.; Kumar, R.; Bonoiu, A.; Prasad, P. (American Chemical Society, 2010)
Carbon nanoparticles become photoluminescent upon surface passivation with oligomeric polymer chains. In this work, the dependence of the carbon dots photoluminescent properties on the passivation polymer selection has been demonstrated by conjugating polyethylene glycol (PEG) chains, polyethylenimide-co-polyethylene glycol-co-polyethylenimide copolymer, and 4-armed PEG molecules, respectively. The cytotoxicity and cellular internalization of the resulting three types of photoluminescent nanoformulations of carbon dots, named CD2, CD3, and CD4, were evaluated. These nanoformulations exhibited no apparent cytotoxicity on their own and were shown to successfully target cancer cells by conjugation with transferrin. The implication to the use of carbon dots as biocompatible optical nanoprobes for in vitro cancer diagnostics is discussed.